2019
DOI: 10.22207/jpam.13.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Metallo-β-lactamase Genes among Acinetobacter baumannii Isolated from Different Clinical Samples

Abstract: Acinetobacter baumannii became a serious endemic and widespread pathogen responsible for causing nosocomial infections due to restricted treatment options. This study was conducted to evaluate the role of both antibiotic resistance and genetic pattern in infection caused by MBLs resistance A. baumannii isolated in Baghdad hospitals. Finally, developing selective media in order to detect multidrug resistance A. baumannii isolates according to colony shape appearance changing. Collected 124 isolates from various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Biofilm formation and regulatory genes have been investigated as controversial and critical issues in healthcare settings. However, in some studies, no apparent relationship between β-lactamase enzymes and biofilm formation has been detected 21,22 . Further, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation and regulatory genes have been investigated as controversial and critical issues in healthcare settings. However, in some studies, no apparent relationship between β-lactamase enzymes and biofilm formation has been detected 21,22 . Further, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the results of various studies we determine a significant relationship between β-lactamase enzymes and biofilm operons in A. baumannii 24,27 . However, some researcher showed that there is no significant relationship between biofilm formation and β-lactamase enzymes in P. aeruginosa 22 . This is in contrast to our results, which confirm that the biofilm regulatory gene in P. aeruginosa is most abundant in the β-lactamase producing strains (~35% in resistant vs. ~11% in susceptible, p< 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the majority of A. baumannii 99% were resistant to ciprofloxacin, 98% were resistance to ceftazidime, meropenem, and imipenem, 77% were not sensitive to gentamicin, and 48% were resistance to amikacin 36 . Our results showed that most of A. baumannii isolates 98.5% were highly susceptible to colistin, as it mainly targets the LPS components, and attenuates the colonization of A. baumannii in lung epithelial cells 37 .…”
Section: Discussionmentioning
confidence: 68%
“…Outer-membrane proteins: (OmpA, Omp 22) Adherence and invasion, apoptosis induction, biofilm formation, persistence, and serum resistance. [17,18] Lipopolysaccharide (LPS) Serum resistance, survival during tissue infection, evasion of immune system response. [18,19] Micronutrient Acquisition System (iron, manganese and zinc) Competition and survival cause the death of host cells.…”
Section: Virulence Factor Activity In Pathogenesis Referencementioning
confidence: 99%